The value of ultrasound and color Doppler ultrasonography in the evaluation of periapical lesions in comparison to histopathological and/or surgical findings - Mithaq A Zebun; Ahlam A Fattah (College of Dentistry/ University of Baghdad, 2014)
Background: Imaging techniques play a very important role in the specialty of endodontic. The ultrasonographic technique is non-expensive procedure, safe, and reproducible. The aim of the study was to determine the sensitivity, specificity, and accuracy of ultrasound and color Doppler ultrasonography in evaluation of periapical lesions (cyst, granuloma, mixed lesion cyst within graulomas mass, and abscess. Subject, Material and method: The sample consists of prospective study for 64 Iraqi participants who attended Karbalaa Specialized Center for Dentistry (males & females). Those patients were diagnosed clinically and radiographically as having periapical lesions of dental origin. They were examined by real time ultrasound and color Doppler ultrasonography with echographic predilection about the type of the lesion based on three parameters measured by ultrasound including: content, outline, and the vascularity. The echographic diagnosis was compared to the final histopathological and /or surgical findings obtained from the periapical surgeries. Results: The sensitivity, specificity and accuracy of ultrasound diagnosis were respectively as follow: for periapical cyst, they were 92.3%, 96.1%, and 95.3%. While for periapical granulomam, they were 87.0%, 92.7%, and 90.6%. For mixed lesions, they were 66.7%, 98.4%, and 96.9% and lastly for periapical abscess, they were 92.0%, 97.4%, and 95.3%. The ultrasound diagnosis in our study had an overall agreement of 89% between ultrasound diagnosis and final diagnosis based on histopathological and/ or surgical findings. Conclusion: Ultrasound is a non- invasive, low cost, and complementary method for examination and diagnosis of periapical lesions and there is correlation of ultrasonographic findings with histopathological and /or surgical findings for final diagnosis.